Functional neurological disorders in patients with brain tumours. (15th October 2021) - Toh, Charmaine; Joe, Dorothy; Cikurel, Katia; Johnson, Julia; Vergani, Francesco; Lavrador, Jose-Pedro; Bhangoo, Ranjeev; Ashkan, Keyoumars; Shotbolt, Paul; Khan-Bourne, Najma; Finnerty, Gerald
Abstract: Aims: Signs and symptoms that develop in people with brain tumours are often attributed to their tumour. The prevalence and management of functional neurological symptoms in brain tumour patients have received little attention. This is surprising because functional neurological symptoms complicate management greatly and misdiagnosis can lead to inappropriate treatment and iatrogenic side-effects. Therefore, we investigated the presentation, diagnosis and management of functional neurological disorders (FND) in patients who had a brain or meningeal tumour. Method: A retrospective case review was performed from 2017 - 2021 to identify adult brain tumour patients who developed a functional neurological disorder that caused significant disability necessitating expedited investigations. All patients attended a regional neuro-oncology centre. We recorded type of brain tumour and diagnostic investigations. The onset of functional symptoms was divided into three time windows: before tumour diagnosis, after diagnosis and before treatment or after tumour treatment. A neuropsychological review looked for evidence of previous adverse life events. Therapeutic interventions for functional neurological disorder and their outcomes were documented. The case review was combined with a systematic review of the literature to identify the published presentations of functional neurological disorder in the adult brain tumour population. MEDLINE, EMBASE and PsycINFO databases were searched for studies published between January 1980 and February 2021. Results: Six patients (5 female, 1 male) were identified from the case review with a median age of 41 (range 29 - 56) years old. Four patients had non-epileptic attack disorder, which was diagnosed with videotelemetry of habitual attacks. One patient had a functional hemiparesis with normal central motor conduction time. One patient had a functional speech disorder with normal EEG. Half of these patients had functional neurological symptoms prior to surgery/oncological treatment. Five patients (83%) were referred for further neuropsychiatric or psychological evaluation. A history of significant psychological trauma prior to the brain tumour diagnosis was elicited in four (66%) patients. Conclusion: Patients with either a brain or meningeal tumour may develop functional neurological symptoms. Our findings suggest the possibility that diagnosis of a brain tumour may precipitate a debilitating functional neurological disorder. The neurobiological basis for functional neurological disorders is being actively investigated. There are suggestions in the literature that some brain diseases increase the risk of developing a functional neurological disorder. Further work is needed to determine whether this is true for patients with brain tumours. Increased awareness of functional neurological disorders will improve management. Withdrawal of unnecessary treatment, such as anticonvulsant drugs, reduces the risk of iatrogenic side effects. Initiation of multi-disciplinary care pathways, e.g. physiotherapy, speech and language therapy and psychological treatments, promotes recovery. Collectively, these interventions improve our patients' quality of life.